Nephrotoxic Effects of Calcium Carbide on Wistar Albino Rats – A Histological Study - Yadav , Gita Kumari; Shrestha , Shamsher; Yadav, Prabhakar; Pokhrel, Churamani (Europasian Journal of Medical Sciences, 2024)
Background: Calcium carbide (CaC2) is commonly used as an artificial fruit ripening agent. Once CaC2 comes in contact with moisture, it releases acetylene gas (Carbide gas), similar to the fruit ripening agent ‘ethylene’. The main objective of the study was to investigate the effect of calcium carbide on the kidney via the evaluation of gross and histological changes. Data & Methods: Twenty-four male healthy Wistar-albino rats weighing 130-200gm were randomly divided into 4 groups i.e. control group (received normal diet) and group I (normal diet mixed with 0.5gm CaC2), group II (received normal diet mixed with 0.25gm CaC2), group III (normal diet mixed with 0.125gm CaC2). Each group included 6 rats. All groups were treated over 21 consecutive days. On the 22nd day, all rats were anesthetized by inhalation of ether and scarified by cervical dislocation. Organs were removed and preserved in 10% formalin solution for histological examination. The diameters of renal components were measured using oculo-micrometers. Results: CaC2 did not affect the body weight of albino rats. Compared to the control group, the weight of kidney of all experimental groups decreased significantly (p-value 0.001). Histological study of the kidney showed a statistically significant decrease in the diameter of renal corpuscle and capsular space of group I compared to the control group and a statically significant increase in diameter of that of group II and III (p-value <0.01). The diameter of the glomerulus of group I and group III decreased but that of group II diameter was increased compared to the control group (p-value <0.01). Similarly, the diameter of distal convoluted tubules decreased in all experimental groups (p-value <0.001). However, there was no effect in the diameter of proximal convoluted tubules of all experimental groups (p-value 0.052). Conclusion: CaC2 caused both morphological and histological changes in rat kidney.